Administrative Creativity In Soccer Premier League Clubs' Administrative Bureau - Hamad, Thamer; Saad, Samer (Journal of Physical Education, 2019)
The importance of the research lies in making an analytical study of administrative creative procedures in soccer primer league clubs in Baghdad. The aim of the research was to construct and standardize a scale for measuring administrative creativity as well as identifying the level of the current administrative bureau. The researchers used the descriptive method on (35) soccer primer league clubs taking (184) administrative member. The scale consisted of (36) item distributed on (7) fields applied on (90) members. The data was collected and treated using SPSS to conclude that administrative creativity was not apparent thus gained (fair) level due to lack of creativity. The researchers recommended applying the scale continuously as a reference for improvement and development and stressing team creativity and interaction to improve the work of this bureau.